Regicide - Royle, Nicholas, 1963- (Solaris, 2011)
"Carl meets Annie Risk and falls for her. Hurt by a recent relationship, she resists becoming involved. A chance find offers distraction. Carl stumbles across part of a map to an unknown town. He becomes convinced it represents the city of his dreams, where ice skaters turn quintuple loops and trumpeters hit impossibly high notes ... where Annie Risk will agree to see him again. But if he ever finds himself in the streets on his map, will they turn out to be the land of his dreams or the world of his worst nightmares?"--Back cover